Pelatihan Manajemen Organisasi dan Motivasi Kewirausahaan Bagi Pengurus Paskibra Periode 2023/2024 Kota Bandung - Dudi Darmawan, Eki; Sudrartono, Tiris; Legistari, Kartika; Triswastika, Arimbi; Insani, Siti; Karyadi; Paryanti, Dini (LPPM Politeknik Piksi Ganesha, 2024)
Organisational Management Training and Entrepreneurial Motivation to the management of the Bandung City Paskibra aims to improve skills in managing organisations and increasing entrepreneurial motivation for young people, especially for the management of the Bandung city paskibra who are also high school students in class XI in the Bandung City area. The training method is in the form of lectures delivering material and question and answer discussions this aims to make the training more effective and efficient in receiving the participants, After the training was carried out on organisational management and entrepreneurial motivation, there was an increase in insight and motivation from the participants as seen from the evaluation results before the training was carried out as many as 20 participants obtained score scores below 80 and after the training increased as many as 15 participants obtained score scores above 90 and 5 participants obtained scores between 80 to 89. This training is very useful and needs to be re-conducted in the future for the younger generation